Analysis of the fluorescence of mechanically processed defect-laden hexagonal boron nitride and the role of oxygen in catalyst deactivation. (19th May 2019) - Nash, David J.; Chagoya, Katerina L.; Felix, Alan; Torres-Davila, Fernand E.; Jiang, Tao; Le, Duy; Tetard, Laurene; Rahman, Talat S.; Blair, Richard G.
ABSTRACT: The use of hexagonal boron nitride ( h -BN) as a non-metal heterogeneous catalyst has been a popular subject in research since the discovery of its catalytic properties in 2016. Previous work found that an activation step was necessary for producing an effective catalyst. Density functional theory (DFT) calculations indicate defect sites, such as nitrogen (VN ) and boron (VB ) vacancies, bind favourably to olefins, hydrogen, and oxygen. In particular, the visible fluorescence intensity of processed h -BN increased with the length of exposure to air. The fluorescence behaviour of dh -BN powders when exposed to air after exposure to species such as argon, propene, and carbon dioxide is presented. Density of state calculations for molecular and atomic oxygen bound to VN and VB show that this increase in fluorescence may be due to atomic oxygen binding to VN . The fluorescence emission behaviour observed in dh -BN powders and its relationship to DOS of oxygen species bound to catalytically active defect sites provides a better understanding of potential deactivation modes for catalysts based on dh -BN.